Extracellular domain of HER2 heterologous expression in bacteria - V. V. Dolgikh; I. V. Senderskiy,; G. V. Tetz; V. V. Tetz (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
Human epidermal growth factor receptor (HER2/neu, c ErbB2) is a protooncogene protein which is overexpressed in some oncological diseases including 30 % of breast cancers, tumors in the ovary, stomach and other organs of the human body as well. Since Her2tumor status testing is the essential part of successful cancer treatment, expression and purification of substantial amounts of the extracellular domain of the ECD HER2 is an important task. In this work sequence encoding HER2 extracellular domain was cloned and expressed in E.coli.